CLASSROOM MANAGEMENT IN INCREASING STUDENTS' INTEREST IN LEARNING AT MADRASAH ALIYAH AL-MUKHLISHIN BATU BARA - Neliwati, Neliwati; Akbar, M. Ali; Nur, M. Ridhona Z.; Gemilang, Cindi (Universitas Indraprasta PGRI, 2025)
Classroom management encompasses all teacher actions that aim to establish and maintain optimal conditions for teaching and learning, thereby increasing student engagement in the educational process. This study used qualitative research in a descriptive format, focusing on homeroom teachers and grade X students as subjects. Data collection strategies included observation, interviews and documentation. The study findings show that classroom management strategies to increase student engagement involve careful preparation of educational resources, including lesson plans, using diverse teaching methods, and connecting students with real-world experiences to make learning fun rather than boring. The implementation of classroom management to increase students' interest in learning involves teachers using diverse teaching methods, continuously refining appropriate learning models and being prepared to help students, thereby promoting increased student engagement and optimising educational outcomes. Constraints and challenges in classroom management that affect student engagement in learning occur during the last hour of teaching and during key discussions or material that students find challenging. In addition, the limited provision of resources exacerbates the decline in students' interest in learning.